Analysis of Seawater Quality on the Sustainability of Seaweed Cultivation on the coast of Nusa Penida, Bali - Nyoman Sudipa (Advances in Tropical Biodiversity and Environmental Sciences, 2024)
Seaweed is a valuable economic resource for the coastal communities of Nusa Penida, which can significantly improve people's lives. Seaweed's existence depends on the quality of the coastal waters of Nusa Penida. This study aims to assess the Nusa Penida coast in support of the sustainability of seaweed cultivation. This research uses a quantitative approach to analyze seawater quality. The results of the calculation of the pollution index show that the seawater quality on the coast of Nusa Penida is in excellent condition, meeting water quality standards based on water quality standards for marine biota by the Regulation of the Governor of Bali No. 16 of 2016 concerning Environmental Quality Standards and Quality Standard Criteria for Environmental Damage, which means that it is very feasible for seaweed culture. The factors that influence the marine water pollution index include TDS, ammonia, and nitrite levels in Jungutbatu seawater; nitrite levels in Toyapakeh seawater; TDS, ammonia, and nitrite levels in Penida seawater; nitrite levels in Buyuk Kutampi seawater; ammonia and nitrite levels in Sampalan seawater; and nitrite levels in Suana seawater.